Management of Post Menstrual Syndromes: From Traditional Knowledge to Evidence-Based Medicine - Mahomoodally, M. Fawzi (International Journal of Biotechnology for Wellness Industries, 2013)
Plants were and are still widely used for a number of pathologies affecting women health, particularly post menstrual syndromes (PMS). PMS refers to a diverse set of clinical symptoms and nearly omnipresent in the woman of reproductive age and can impinge on women’s interpersonal relationships, social behavior, work absenteeism, and work productivity [1]. In addition to conventional FDA approved drugs, a plethora of other selections are imperative to reflect on for women who prefer natural alternative and complementary therapies or for whom conventional remedies are contraindicated [2]. Indeed, prior to the introduction of modern therapy, a panoply of medicinal herbs such as Kacip Fatima, Vitex, Yam, Licorice, Alfalfa, Chamomile, Dong-Quai, Evening Primrose, Ginkgo, Water-Willow and Cohosh have been used predominantly to treat or relief PMS. Traditional Chinese medicine has been prescribing herbs and herbal formulas since time immemorial; for instance Angelica (Dang Gui) has been widely used by Chinese and Japanese women for centuries. It is well-known for regulating menstrual cycles, eliminating the discomfort of premenstrual syndromes, and relieving menstrual cramps. Medicinal plants thus tend to represent a safe alternative to current hormone or drug therapy used to manage PMS symptoms. Many of these herbals formulas were geared towards regulating hormonal cycle and some recently being reported to have estrogen and/or progesterone-like effects [3-5]. Other less popular herbs that have been used successfully to decrease nervous tension include passion-flower, valerian, oat-grass, lemon-balm and skull-cap [6]. One phytotherapeutic combination; dandelion root/leaf- Taraxum officinale, milk or blessed thistle- Cnicus benedictus, Vitex- Vitex agnus-castus, black or blue Cohosh- Cimcifuga racemosa and Caulophylum thalictroides, Dong-Quai - Angelica sinensis and wild-Yam - Dioscorea villosa, is prescribed by phytotherapists and/or traditional healers as a polyherbal tea (1 tsp. of the herbal formula, one part each, in 1 cup of boiling water thrice daily) or in tincture (1/2 tsp. 3 to 4 times daily). However, Vitex also known as chaste tree berry, has attracted much consideration and comprehensively tested in randomized controlled trials; [1, 7-8] and reported to exhibit dopaminic agonist, inhibiting prolactin and increasing estrogen secretions and its flavonoids ligands to benzodiazepine receptors- thereby depicting antidepressant and anxiolytic properties [1]. Chaste berry fruit extract has also been shown to correct prolactin levels in latent hyperprolactinaemia via dopamine receptors. Vitex formulation (Agnolyt®) has been reported to be superior to pyridoxine in reducing premenstrual tension, whereas Femicur® (dried extract of Vitex) decreased and/or ceased mastalgia, associated to PMS; both tested in randomized controlled clinical trials [7, 8]. Nonetheless, many of the above-mentioned mono or poly-phytotherapeutic combinations are not recommended during pregnancy and possible hormonal effects through breast milk (some via prolactin inhibition) [3]. Additionally, extensive and scientific-based clinical research into the use of herbal therapies for premenstrual disorders, specifically in adolescents is unfortunately sparse. To this effect, phytotherapies for PMS can be given due consideration provided they are prescribed by trained professionals following rigorous high-quality clinical testing and with optimal dosing standards but avoided concurrently with conventional medications. Additionally, it is believed that it is of uttermost importance for medical practitioners to be aware of such herbal therapies and any innate potential drug-herb interactions and/or side effects in an endeavor to offer alternatives to women.